P630 Inflammatory bowel disease in immigrants to Spain: results of the EIIMIGRA study from GETECCU (ENEIDA registry). (27th May 2021) - Gutiérrez Casbas, A; Zapater, P; Ricart, E; González-Vivó, M; Gordillo, J; Olivares, D; Vera-Mendoza, I; Mañosa, M; Gisbert, J P; Aguas, M; Sánchez-Rodríguez, E; Boscá, M; et al.
Abstract: Background: Previous studies comparing inflammatory bowel disease(IBD) features between migrant and native patients have shown clinical phenotype differences. To date, no study has focused on IBD immigrants(MP) in Spain. The aim of this study was to explore the features of MP in Spain and to compare age of disease onset, IBD phenotype and therapeutic requirements with native-born IBD patients(NP). Methods: This was an observational, multicentric and case-control study of the nationwide ENEIDA registry. We selected all IBD patients who were born outside of Spain and compared with a control cohort of NP. All included patients were diagnosed with IBD before 2015. Results: A total of 13, 524 patients were included(1864 MP and 11660 NP).The most prevalent ethnic migrant group was Caucasian(771, 41%), followed by Latin American(572, 31%) and Arabian(341, 18%), whereas Asian represented only 6%. Table 1 summarizes the demographic and phenotypic features. 71% of MP were diagnosed with IBD in Spain. There was not a gender predisposition to IBD in the overall migrant group, however more female UC MP were detected compared to UC NP(52 % vs 45%, p<0.001). MP were younger at the onset of the disease and had a shorter disease duration compared to NP, in both UC and CD patients. Significantly more CD patients were diagnosed under 16 years(A1) among MP, and more patients over 40 years(A3) among NB. More NB patients had CD stricturing phenotype(24% vs 19%, p=0, 002) compared to MP. Disease extension in CD and UC did not differ between groups. The overall proportion of abdominal or perianal surgery was similar in both groups but the use of biologic therapy was more common in MP(36% vs 30%, p=0, 001). Conclusion: In the largest cohort of migrant IBD patients in Spain, immigrants were younger, had a shorter disease duration and required a higher use of biologics than natives, pointing phenotypic differences in this population and a universal access to the healthcare system all over the country.